The Multicriteria Assessment of the Green Growth in the Context of the European Union’s Green Deal - Doskočil, Radek (Bucharest University of Economic Studies, 2022)
The article deals with the issue of assessment of the green growth in context of the Green Deal in the European Union Countries. Because this issue leads to the decision problem which has typical the properties of multi-criteria decision making (MCDM), the Analytical Hierarchy Process (AHP) method, including the sensitivity analysis, was used as a suitable method for solving this issue. The main aim of the paper is to propose a new and suitable approach for a complex and systematically assessed Green Growth in countries of the European Union. The public OECD Green Growth database was used for the analysis. The multicriteria assessment model employs four criteria, indicators for monitoring progress towards green growth (1. Production-based CO2 productivity; 2. Annual surface temperature; 3. The mean exposure of the population exposure to PM2.5; 4. Environmentally related tax). Thanks to the new approach to the Green Growth assessment based on multicriteria evaluation, it is possible to automate this process and it is repeatedly applied. This ultimately provides management authorities with a tool to measure the maturity of the Green Deal not only in EU countries. Based on the proposed multi-criteria model, Ireland is evaluated as the land with the highest level of Green Growth and Latvia as the country with the lowest level in the analyzed year 2020.

The article deals with the issue of assessment of the green growth in context of the Green Deal in the European Union Countries. Because this issue leads to the decision problem which has typical the properties of multi-criteria decision making (MCDM), the Analytical Hierarchy Process (AHP) method, including the sensitivity analysis, was used as a suitable method for solving this issue. The main aim of the paper is to propose a new and suitable approach for a complex and systematically assessed Green Growth in countries of the European Union. The public OECD Green Growth database was used for the analysis. The multicriteria assessment model employs four criteria, indicators for monitoring progress towards green growth (1. Production-based CO2 productivity; 2. Annual surface temperature; 3. The mean exposure of the population exposure to PM2.5; 4. Environmentally related tax). Thanks to the new approach to the Green Growth assessment based on multicriteria evaluation, it is possible to automate this process and it is repeatedly applied. This ultimately provides management authorities with a tool to measure the maturity of the Green Deal not only in EU countries. Based on the proposed multi-criteria model, Ireland is evaluated as the land with the highest level of Green Growth and Latvia as the country with the lowest level in the analyzed year 2020.
The Multicriteria Assessment of the Green Growth in the Context of the European Union’s Green Deal
Keywords: Green Deal; Green Growth; indicators; multicriteria decision-making; AHP (Analytical Hierarchy Process) method; OECD.; Green Deal; Green Growth; indicators; multicriteria decision-making; AHP (Analytical Hierarchy Process) method; OECD.